Characterization of an aerated submerged hollow fiber ultrafiltration device for efficient microalgae harvesting. Issue 10 (12th September 2021) - Ortiz Tena, Franziska; Ranglová, Karolína; Kubač, David; Steinweg, Christian; Thomson, Claudia; Masojidek, Jiří; Posten, Clemens
Abstract: The present work characterizes a submerged aerated hollow fiber polyvinylidene fluorid (PVDF) membrane (0.03 μm) device ( Harvester ) designed for the ultrafiltration (UF) of microalgae suspensions. Commercial baker's yeast served as model suspension to investigate the influence of the aeration rate of the hollow fibers on the critical flux (CF, J c ) for different cell concentrations. An optimal aeration rate of 1.25 vvm was determined. Moreover, the CF was evaluated using two different Chlorella cultures (axenic and non‐axenic) of various biomass densities (0.8–17.5 g DW/L). Comparably high CFs of 15.57 and 10.08 L/m/ 2 /h were measured for microalgae concentrations of 4.8 and 10.0 g DW/L, respectively, applying very strict CF criteria. Furthermore, the J c ‐values correlated (negative) linearly with the biomass concentration (0.8–10.0 g DW/L). Concentration factors between 2.8 and 12.4 and volumetric reduction factors varying from 3.5 to 11.5 could be achieved in short‐term filtration, whereat a stable filtration handling biomass concentrations up to 40.0 g DW/L was feasible. Measures for fouling control (aeration of membrane fibers, periodic backflushing) have thus been proven to be successful. Estimations on energy consumption revealed very low energy demand of 17.97 kJ/m 3 treated microalgae feed suspension (4.99 × 10 −3 kWh/m 3 ) and 37.83 kJ/kg treated biomass (1.05 × 10 −2 kWh/kg), respectively, for an up‐concentration from 2 to 40 g DW/L of a microalgae suspension.